THE ARTISTRY OF MIRROR EMBELLISHMENTS IN FASHION - Rayalwar, Jahnavi; Mokanaasri, E (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mirror work is a traditional textile embellishment technique that involves stitching small pieces of reflective material, often mirrors, onto fabric. This intricate craft has been used for centuries to adorn garments, particularly in Indian culture, where it is believed to ward off evil and bring good luck. This style combines traditional craftsmanship with modern manufacturing methods, producing high-quality, market-ready products. Digital design techniques have streamlined the process, enabling precise and repeated patterns that enhance the visual appeal. This fusion of traditional craftsmanship with contemporary technology exemplifies the potential for innovation in the textile industry. This study explores the historical significance, Global Designers and Innovation in mirror work, various types of mirror work, techniques, variations used in the fashion fields, and different methods of attaching mirrors to fabric, including frames for the mirror. This study also discusses the applications of mirror work in fashion, highlighting its use in traditional and trendy garments. The fusion of mirror works into textile designs, informed by extensive secondary data, has led to the development of innovative and aesthetically pleasing products.